Making Sense of Thailand's "Merit-Making" Muslims: Adoption and Adaption of the Indic in the Creation of Islamicate Southern Thailand - Christopher M. Joll (2018)
This article presents an alternative to the analysis of Thai merit-making rhetoric (tham bun) that associates it with Theravada Buddhism and syncretic anomalies. A review of the processes through which Islam became an authentically Southeast Asian religion suggests that this merit-making conundrum is a recent example of the adoption and adaptation of Indic terms by Southeast Asian Muslims. These were central to the creation of Islamicate cultures. The concepts Indic and Islamicate are capable of pushing through conceptual cul-de-sacs such as syncretism and shared cosmologies. In addition to the specific generation of merit erroneously assumed as its only meaning, the article reveals that tham bun also denotes undifferentiated religious actions, and is code for a range of feasts unrelated to merit-making. It argues that the co-option of tham bun by Thai-speaking Muslims is an example of a search for equivalents. It also suggests the presence of an authentically Islamic economy of merit in Southern Thailand, confirming Islam's ability to speak the language of Indic Southeast Asians and to scratch where they itch. © 2014 University of Birmingham.